Analisis Pengaruh Perubahan Tata Guna Lahan Terhadap Debit Banjir Pada Wilayah Hilir DAS Saddang Kabupaten Pinrang - Ocktaviani, Salsabila Nada; Badrun, Burhanuddin; Cangara, Satriawati (Program Studi Teknik Sipil Universitas Bosowa, 2025)
The primary causes of watershed degradation are the loss of vegetation in permanent land/forests and the inappropriate use of land. Given the current condition of the Saddang River, it is highly susceptible to flooding, especially during periods of heavy rainfall. This situation is exacerbated by changes in land use. Flooding in the Saddang watershed occurs almost annually during the rainy season, particularly in the lower reaches encompassing the districts of Duampanua, Cempa, and Patampanua. This study aims to determine the impact of land use changes on flood discharge in the lower reaches of the Saddang watershed. The research employed a quantitative approach, utilizing daily rainfall data for hydrological analysis and land cover data for land use change analysis. The Mononobe method was used to calculate rainfall intensity, while the Nakayasu Synthetic Unit Hydrograph (SUH) method was applied to compute design flood discharge. The results revealed a 7.79% change in land use between 2012 and 2021. This change led to an increase in the surface runoff coefficient (C). Consequently, there was an 8.93% increase in flood discharge during the 2012-2021 period, attributed to the higher runoff coefficient resulting from land use changes.